Design of Educational Technologies in the Development of Professional Competences of Technology Teachers - Haydarov Ramozon Mamayusupovich (Genius Publishing Group, 2022)
The article highlights the importance of shaping students' knowledge, skills and competencies through the use of educational technology in technology lessons.
Keywords: Metal; interactive methods; processing; training